HYDROGEN ISOTOPIC COMPOSITION OF BACTERIAL METHANE: CO2H2 REDUCTION AND ACETATE FERMENTATION - Sugimoto A.; Wada E. (My University, 1995)
In order to discern the δDwater-δDCH4 relationship betweenCO22 reduction and acetate fermentation in freshwater environments where CH4 is produced from both CO22 and acetate, incubation experiments of a paddy soil were made, using water with four different δD values. From the observed δDwater-δDCH4 relationships and a fractional contribution of acetate estimated from δ14C of CH4, δDwater-δDCH4 relationships were obtained forCO22 reduction and for acetate fermentation, respectively. The relationships were expressed as follows:δDCH4(CO2) = (0.683 +/- 0.020)δDwater - (317 +/- 20)δDCH4(Ac) = (0.437 +/- 0.045)δDwater - (302 +/- 15).The obtained difference in δD between freshwater and CH4 from CO22 (317%%) was much larger than that reported in marine sediments (180%%). Accordingly, no significant difference in δD of CH4 betweenCO22 reduction and acetate fermentation is expected when the δD of water is close to SMOW, and δD of CH4 from CO22 is lower than that from acetate when the δD of water is low. The large fractionation obtained for CO22 reduction may be caused by a high H2 concentration in the freshwater soil which is rich in easily decomposable organic matters. The estimated slope (0.437) of the δDwater-δDCH4 relationship for acetate fermentation indicates that some of the hydrogen atoms in the methyl group of acetate exchanged with water during the acetate production.On the basis of the experimental results, the range of δD-δ13C for CH4 fromCO22 reduction and that for acetate fermentation were calculated for the freshwater environments. Although only a negative correlation between δD and δ13C of CH4 has been expected, our results indicate the possibility of a positive correlation between them in freshwater areas.